(3GdESdGejhf dLRGFQjhf Hjf GdSdWI h GdQUGU (B/s - (3YjGTj,GMejOI s ([(3Ohf ecGf(B] :s (3OGQ GdMceI ddJQLeI h GdfTQ ,s, 1992)
(3aj gPG GdcJGH jLO GdbGQF GdYOjO ef GdeYWjGJ Mhd LhGf(B91 -(3RhHYI GdOe h GdJehjd (B..(3ehba GdfgVI h MeGS ef GdMUGQ(B- (3GdEVQGH GdYGe h eGSGI LhGf (B..(3HhjYdj(B: (3GdhLg GdLRGFQjddESdGe GdeSdM HdMGL Gh GdejKGdjI GdKhQjI h aj gPg jLO GdbGQF GdhKjbI GdcGedI ddMUGQ GdeOfj s
Keywords: (3GdMQcI GdESdGejIs